Macrophages in acne vulgaris: mediating phagocytosis, inflammation, scar formation, and therapeutic implications - Feng, Yibo; Li, Jiaqi; Mo, Xiaohui; Ju, Qiang (Frontiers in Immunology, 2024)
Macrophages serve as a pivotal nexus in the pathogenesis of acne vulgaris, orchestrating both the elimination of Cutibacterium acnes (C. acnes) and lipid metabolic regulation while also possessing the capacity to exacerbate inflammation and induce cutaneous scarring. Additionally, recent investigations underscore the therapeutic potential inherent in macrophage modulation and challenge current anti-inflammatory strategies for acne vulgaris. This review distills contemporary advances, specifically examining the dual roles of macrophages, underlying regulatory frameworks, and emergent therapeutic avenues. Such nuanced insights hold the promise of guiding future explorations into the molecular etiology of acne and the development of more efficacious treatment modalities.